Association between polymicrobial infections and severity of diabetic foot infection among patients in Hospital Universiti Sains Malaysia - Hitam, Sharifah Aisyah Sayed (2016)
Background: Foot infections are a major complication of patients with diabetes mellitus (DM). The causative microorganisms are usually polymicrobial.The aim of the study is to determine the percentage of microorganism in diabetic foot infection, its susceptibility to antibiotic, association between polymicrobial infection and severity of diabetic foot infection and to determine the outcome of diabetic foot infection among patients infected with polymicrobial organisms in Hospital USM. Materials and methods: This is a retrospective analysis conducted for one year duration starting from June 2014. A total of 104 patients selected from this study. Their folders were reviewed and assessed for severity and outcome of foot infection in association with polymicrobial infections. Parameters such as glycated haemoglobin (HbA1c), random blood sugar (RBS), total white cell (TWC) and haemoglobin (Hb) were analysed. The result were presented as descriptive and statistically analysed by Fisher exact test.Results: There were 104 patients involved in this study, with a total 133 microorganisms were isolated with an average of 1.28 organisms per lesion. Gram negative (GN) and Gram positive (GP) microorganisms were 62% and 38%respectively.The most frequently isolated GN microorganism includes Pseudomonas spp (28%), Proteus spp (11%), Klebsiella spp (8%) and E. coli (4%). Staphylococcus aureus was the predominant (54%) among GP microorganisms followed by Group B Streptococci (26%) and Enterococcus spp (6%). GN isolates were sensitive to carbapenem and aminoglycoside groups while vancomycin showed good activity to GP microorganism. There was significant association between quantity of microorganisms and severity of diabetic foot infection using Fisher’s Exact test (p=0.003). Thirty patients had polymicrobial infections. In severe diabetic foot infection, 77.8% with polymicrobial organisms undergone amputation, meanwhile monomicrobial infection was 33.3%. Majority of polymicrobial or monomicrobial infection was discharged well, 84.0% and 91.1% respectively. There was no significant association between polymicrobial or monomicrobial infection with patient’s outcome of severe diabetic foot infection including amputation and discharge of patient (p=0.136 and p=0.465). The mean (SD) for HbA1c, RBS, TWC and Hb in severe polymicrobial infections were 11.8(2.1) %, 16.3 (5.2) mmol/L, 16.6 (2.4) x 109 and 9.0 (1.3) g/dL respectively. Conclusion: GN microorganisms were predominantly isolated from diabetic foot infections and antibiogram showed that the common organisms remain sensitive to a number of widely used agents. Polymicrobial infections were associated with theseverity of its infection meanwhile quantities of organisms was not associated with patient’s outcome of diabetic foot infection. There were higher glucose level and TWC count with lower Hb in severe polymicrobial diabetic foot infection.